GEOLOCATION AND BIOSECURITY OF LAYER FARMS AND THEIR REPLACEMENTS IN THE POULTRY COMPANY OF MATANZAS PROVINCE, CUBA - Torres-Herrera, Javier (2021)
The objective of the work was to establish the georeferencing and evaluate the biosecurity of the layer farms and their replacements of the PioMat Poultry Company. A cross-sectional observational research was carried out in 10 Basic State Units (BSU) of laying hens and five of replacements in the Matanzas province, Cuba during a period of eight weeks, from March to May 2019. The data, epizootiological quadrants, identification was recorded. of the BSU, total number of rearing houses, orientation of the houses, distance and location of nearby towns and roads and for the spatial visualization the QGIS version 3.0.1 program was used. A comparison of proportions analysis was performed using the COMPAPROP statistical package. A significant high proportion of laying BSU sheds located incorrectly “N-S” was observed, with respect to the correct “NW-SE”. However, the replacement UEBs did not differ significantly from the correct "E-O" ones. Concluding that it was possible to determine the georeferencing of the BSU of laying hens and their replacements as well, as the main vulnerabilities in terms of biosecurity, seeing greater connotation in the raising of laying hens.